К.КАРИМОВТЫҢ «АРАЛДЫҢ ҮМИТИ» РОМАНЫНДА ДИАЛОГ ҲӘМ МОНОЛОГТЫҢ КӨРКЕМЛИК ХЫЗМЕТИ - Нуржанов, П.; Абсаттарова, Н. (FAN va JAMIYAT, 2024)
In the article was studied the importance of dialogue and monologue in K. Karimov’s novel “Aral’s hope”, basically, was studied the problem of the work and the significance of the artistic function in depicting the psyche of the hero were studied.